2021
DOI: 10.48550/arxiv.2104.09204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey on Millimeter-Wave Beamforming Enabled UAV Communications and Networking

Abstract: Unmanned aerial vehicles (UAVs) have found widespread commercial, civilian, and military applications. Wireless communication has always been one of the core technologies for UAV. However, the communication capacity is becoming a bottleneck for UAV to support more challenging application scenarios. The heavily-occupied sub-6 GHz frequency band is not sufficient to meet the ultra high-datatraffic requirements. The utilization of the millimeter-wave (mmWave) frequency bands is a promising direction for UAV commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 333 publications
(481 reference statements)
0
5
0
Order By: Relevance
“…Specifically, beamforming sends the same symbol over each transmit antenna with a weighted scale factor. 47,48 • Massive MIMO: A negative side effect of beamforming is that only devices on the beam path can receive the signal. Massive MIMO addresses this by deploying multiple antenna arrays in all directions to achieve strong signals for all users.…”
Section: G Core Network Architecturementioning
confidence: 99%
“…Specifically, beamforming sends the same symbol over each transmit antenna with a weighted scale factor. 47,48 • Massive MIMO: A negative side effect of beamforming is that only devices on the beam path can receive the signal. Massive MIMO addresses this by deploying multiple antenna arrays in all directions to achieve strong signals for all users.…”
Section: G Core Network Architecturementioning
confidence: 99%
“…There is a growing number of works that integrates UAV into mm-Wave networks due to its promising merits. In [26], the authors provided a comprehensive survey on UAVassisted mm-Wave communications and summarized their main challenges. In [27], the performance evaluation of UAVassisted mm-Wave networks is investigated, where UAVs were deployed as mm-Wave access points communicating with ground users.…”
Section: A Related Work and Motivationmentioning
confidence: 99%
“…Nevertheless, power-limited constraint, which affects the flight time can be taken into account for future studies, and there are some related works that can be found in [59], [60]. Throughout this paper, we assume that problem (26) is always feasible when the QoS requirement of each user will be satisfied if a ij = 1. To simplify the hybrid beamforming design-based UAV relay and user association process in practical systems, we assume that each user can only be associated with only one BS at a time [51].…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no significant difference from routing in omnidirectional aerial ad-hoc networks. Routing schemes for antenna array enabled aerial ad-hoc networks can draw lessons from that designed for omnidirectional aerial ad-hoc networks [189], [193].…”
Section: B Airborne Communicationsmentioning
confidence: 99%